AutoPot: An Innovative Urban Gardening with IoT-enabled Watering System - Mohd Hanifa, Rafizah; Suderman, Muhammad Haiqal; Hamsan, Hanis Nabihah; Amran, Shaza Batrisyia (Multidisciplinary Applied Research and Innovation, 2025)
Urban living environments such as condos, apartments, flats, and other high-rise buildings often lack personal garden spaces, compelling residents to grow plants in pots. Residents who cultivate plants in pots encounter difficulties in regulating watering routines, necessitating irrigation during dry weather while refraining from watering during humid weather. This can be particularly difficult for those with busy work schedules. Therefore, there is a need for an automated watering system to assist them in maintaining optimal soil moisture levels without the constant need for manual intervention. The AutoPot is proposed to address this gap by developing a prototype that leverages IoT technology to optimize watering practices. The AutoPot integrates sensors to monitor soil moisture, humidity, and temperature levels in real-time, automatically activating a water pump when the soil moisture drops below a preset threshold. This study evaluates the AutoPot system based on its efficiency in watering plants by monitoring soil moisture levels. The system’s performance is assessed by its ability to maintain optimal soil moisture, ensuring plants receive adequate water without over- or under-watering. Data collected at regular intervals demonstrate that the AutoPot successfully maintains soil moisture, humidity, and temperature within desired ranges. Future work will explore adaptive algorithms that adjust watering schedules based on soil type, plant species, and growth stages to further optimize water usage and plant health.